A call for co-working – users' expectations regarding learning spaces in higher education. Issue 2 (14th May 2018) - Sankari, Inka; Peltokorpi, Antti; Nenonen, Suvi
Abstract : Purpose: Today, academic work includes increasingly informal and collaborative activities. This research attempts to determine whether stakeholders in the development of learning spaces in higher education could benefit from the principles of co-working space. This paper aims to determine whether a need exists for co-working space as a learning space solution from the viewpoint of academic space users. This determination will be made by examining the following research question: How does the co-working space concept meet user expectations regarding academic space? Design/methodology/approach: The research question is answered by investigating users' experiences of existing learning spaces in higher education in light of future workplace needs. Users' requirements are examined by analysing user experience survey and interviews. The results are confirmed by focus group interviews and examined in the light of co-working space characteristics that are identified in the literature from the viewpoint of workplace management by searching for similarities between descriptions in the literature and the empirical data. Findings: This research suggests that academic space users would appreciate it if the spaces they use would reflect some of the co-working space characteristics. These characteristics are community, multipurpose office, high accessibility and attractive workplace. A less applicable co-working space characteristic is space as service. Research limitations/implications: The results of this study are based on one case, which limits the generalisability of the results. Practical implications: The results provide suggestions for corporate real estate management and stakeholders in academic institutions to consider when renovating outdated spaces. Originality/value: The paper expands the literature on learning spaces in higher education and related practices by linking it with co-working spaces, thereby contributing to a field that has not yet been explored in depth.